Implementasi Radio Broadcasting Oleh Unit Dikyasa Dalam Mencegah Pelanggaran Lalu Lintas Di Wilayah Hukum Polres Sumedang - Rafif Naufal Ardhia (Police Studies Review, 2020)
In the past 3 years traffic violations have often occurred in Sumedang. The Sumedang Regional Police Precinct Unit of Satyasa has a role in the effort to overcome this problem by using a pre-addictive approach to community education then. This study aims to analyze and describe the efforts and factors that influence Radio Broadcasting programs by the Dikyasa Unit in conducting community education then. The research location is in Sumedang Regional Police with a focus on the implementation of radio broadcasting in the community education program. This study uses qualitative methods with descriptive analysis techniques. Using data triangulation (Moleong; 2006: 330) 4 (four) kinds of techniques, namely sources, theories and techniques as well as primary, secondary and tertiary data sources. Data validity is data reduction, data display, conclusion drawing and verification. This research uses the theories and concepts found in chapter 3. The implementation of community health education then through radio broadcasts which is less than optimal causes the number of traffic violations to remain high. The conclusion is that if community education is often done, the community will be educated, and the number of violations and traffic will be reduced.